The Optimization of Sulphide Oxidizing Bacteria (SOB) for Oil Corrosivity Reduction at Indramayu Coast, The Northern Coastal Area of West Java - Yudi Nurul Ihsan; Kalysta Fellatami; Rega Permana; Jiang Mingguo; Tri Dewi Kusumaningrum Pribadi (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight Research First NR-SOB from Indramayu coast was successfully isolated and identified. Bactrerial characterization morphologically and biochemically, foster with in situ hybridization confirm the isolate was Thiobacillus denitrificans, and Arcobacter sp. Both isolate, Thiobacillus denitrificans and Arcobacter sp., were able to grow in sulphide rich environment in the presence of essential nutrient Thiobacillus denitrificans and Arcobacter sp. exhibit an outstanding sulphide oxidation ability up to 100% in the presence of nitrate. Abstract Crude oil production triggers the formation of hydrogen sulphide, also known as souring, which is extremely toxic and corrosive to the environment. It additionally give an adverse consequence to aquatic, terrestrial, and human existence. Studies of hydrogen sulphide reduction in sediments polluted by crude oil have been carried out recently to investigate the capability of indigenous Nitrate-Reducing Sulphide Oxidising Bacteria, hereinafter referred to as NR-SOB, as bioremediation agents. The experiments utilised hydrogen sulphide with 200 µM concentration combined with NO3 with different concentrations of 100 µM, 200 µM, and 300 µM. Measurements of the hydrogen sulfide concentrations were observed up to 48 hours within the experimental period. The SOB used in this study were taken from Balongan Bay at Indramayu coast using Nansen bottle to carry out water sample. The sulphide-oxidising ability of SOB was then evaluated at room temperature in control environment. Methylene blue method was applied to monitor the sulphide concentration. The results showed a complete removal of hydrogen sulphide concentrations in 48 hours accompanied with gradual drops of nitrate in all experiment series. Sulphide oxidation rate was detected to appear between 6.8 and 10.2 fmol/cell/hour. Measurements of cell abundance after 48 hours showed 6.2 x 105, 7.5 X 105, and 8.2 X 105 cell/ml from Experiments I, II, and III respectively. Using MSS selective medium, the bacteria were identified as Thiobacillus denitrificans and Arcobacter sp. Overall, the isolated NR-SOB from the coast of Balongan Bay, Indramayu proves to be a promising candidate for sulphide controls and mitigation.